Science E-Modules Learning Based on Sasak Local Wisdom to Enhance the Creative Disposition of Elementary School Students - Rahman, Nanang; Wiranata, Sandra; Haifaturrahmah, Haifaturrahmah; Liswijaya, Liswijaya (Universitas Pendidikan Indonesia, 2025)
Science learning in elementary schools is often perceived as abstract and theoretical. This perception makes it difficult for students to grasp scientific concepts, which may sometimes feel distant from their daily lives. Ideally, science instruction should adopt a contextual approach, allowing students to recognize the relevance of scientific knowledge in their environment. The purpose of this research is to develop a science e-module based on Sasak local wisdom to enhance the creative dispositions of elementary school students. The research design employs a development model encompassing validity, practicality, and effectiveness tests. The limited trial involved 15 students, while the field trial included 42 elementary school students. Validation results indicate that the e-module demonstrates excellent quality in terms of media aspects (80.75%) and material aspects aligned with the curriculum (72.93%). The limited trial revealed high practicality (89.78%), while the field trial showed an increase in post-test scores from 58.78% to 88.31%, with an N-gain score of 0.71. The e-module has proven effective in developing students’ creative dispositions. This research contributes to the integration of local wisdom in digital learning resources by fostering culturally relevant science education while simultaneously enhancing students' creative dispositions and promoting cultural preservation through the embedding of Sasak values.